Material invariant poromechanics properties of shales - Constantinides, Georgios; Ulm, Franz Josef; Abousleiman, Younane N. (My University, 2005)
Is it possible to break natural composite materials down to a scale where materials no longer change from one material to another, and upscale ('nanoengineer') the behavior from the nanoscale to the macroscale of day-to-day engineering applications? - This is the challenging question which is addressed in this paper by means of a combined experimental-theoretical multiscale microporomechanics approach and its application to shales. From this analysis it is found that the existence of material invariant properties (the mechanical 'blueprint') is a consequence of the combination of intermineral surface properties and characteristic packing densities, which dominate the nanomechanical response of colloidal material systems, rather than the much stiffer mineral properties. In return, at larger scales, the behavior of natural composites is a consequence of texture which can explain much of the large diversity of mechanical behavior of shale materials. These observations hold for most natural porous composites: bones, concretes, sandstones, etc., and is the focus of the GeoGenome Project, an international research effort, that aims at 'breaking the code' of all natural composite materials.
Keywords: Composite materials; Shale